Guttate Psoriasis Flare Following the Third Dose of mRNA COVID-19 Vaccine in a 36-Year-Old Male: A Case Report - Samodra, Velia Maya; Hendrawan, I Wayan; Medikawati, I Gusti Agung Ayu Ratna; Anulus, Ayu (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: Psoriasis is a chronic, immune-mediated skin disease known to flare in response to various environmental and immunologic triggers, including infections, stress, medications, and vaccinations. With the global rollout of COVID-19 vaccines, rare instances of psoriatic eruptions have been reported. This study aimed to report the case of guttate psoriasis flare following the third dose of mRNA COVID-19 vaccine in a 36-year-old male. Case Presentation: We report the case of a 36-year-old male with a history of guttate psoriasis that occurred seven years prior, which resolved spontaneously without recurrence. The patient had remained disease-free until five days after receiving a third (booster) dose of an mRNA COVID-19 vaccine, when he developed a sudden, widespread eruption of erythematous, drop-like papules and small plaques, predominantly involving the trunk and extremities. Initial management with topical corticosteroids yielded minimal response. Skin biopsy revealed histopathological features consistent with psoriasis. The patient was subsequently started on low-dose methotrexate, resulting in significant clinical improvement within four weeks. Conclusion: This case highlights the possibility that mRNA COVID-19 vaccination may, in rare cases, trigger guttate psoriasis even in individuals with a remote history of the disease and prolonged remission. While vaccination remains a crucial public health intervention, healthcare providers should remain aware of potential cutaneous adverse events and provide prompt, individualized management to maintain both optimal patient care and public vaccine confidence.